MAHAR DAN UANG PANAIK MASYARAKAT SUKU BUGIS: STUDI TEMATIK AL-QUR’AN - Muhammad Asywar Saleh (Faculty of Ushuluddin UIN Syarif Hidayatullah Jakarta, 2018)
This paper explains about the existence of dowry in the phenomenon of panaik money in the Bugis society, where this practice is different from the concept of dowry in the Qur’an. This research was carried out through phenomenological studies. The study finds that there is the difference between dowry money and panaik money. Mahar itself is a mandatory gift in order to have a woman he wants to marry, even though dowry is not a pillar of marriage. While the panaik money is money for a wedding or an event that is used together for the success of two people being married and witnessed by relatives and friends.